Quantitative assessment of modelling and simulation tools for autonomous navigation of military vehicles over off-road terrains. Issue 3 (15th August 2020) - Cole, Michael; Lucas, Cesar; Kulkarni, Kumar; Carruth, Daniel; Hudson, Christopher; Jayakumar, Paramsothy; Gorsich, David
Autonomous systems are the future of the Army and Ground Vehicle Systems Center has aligned itself accordingly to support unmanned ground vehicle (UGV) development. Physically testing autonomous algorithms and vehicle systems can be expensive and time consuming, a problem addressed by the use of modelling and simulation (M&S) tools. A multitude of both Government owned and commercial off-the-shelf tools (COTS) are widely available, all claim to virtually evaluate autonomous ground vehicles operating on various environments and scenarios. Most of the COTS tools primarily focus on the commercial automotive industry where vehicles are driven in a structured environment. In this paper two M&S tools, viz., Autonomous Navigation Virtual Environment Laboratory (ANVEL) and rover analysis modelling and simulation (ROAMS) are evaluated for military applications, where the demands for navigation include both on-road and off-road, as well as both structured and unstructured environments as a preliminary benchmark.